Analisis WASR (Weight Average Supplier Rate) dalam Penentuan Interest Rate Minimal Pembiayaan - Iskandar Iskandar (EXERO : Journal of Research in Business and Economics, 2022)
Since the beginning of 2021, the trend of Indonesia's economic development is getting better. This resulted in increased demand for credit. For banking and finance, this is an opportunity to increase the surplus. One of the things that makes a surplus of a bank and financial institution is interest income or interest income. The interest rate used in the calculation of PBHT is the average interest weighted against the total remaining debt of the debtor or called Asset WASR (Asset Weight Average Supplier Rate), while the rate used when applying for credit is the Booking Rate whose average is called Booking WASR (Booking Weight Average Supplier Rate). The objectives of this study are: 1) To determine the correlation between Asset WASR and Booking WASR. 2) to know how to determine the submission rate in order to achieve the targeted WASR Asset. The data analysis technique used correlation analysis and regression analysis between Asset WASR and Booking WASR. The analysis tool uses Ms. Excel. The conclusions of this study are: 1) There is a strong correlation between Booking WASR and Asset WASR. 2) The formula for determining the minimum rate in order to get the desired profit from interest income is Rate Pengajuan = (Budget Asset WASR - 0,009696217)/0,934663954